Creative Marketing and Financial Performance of Small Medium Enterprises in Rwanda: A Case Study of Selected Businesses in Nyamata Town. - Tenywa, Bashir (Kabale University, 2023)
The study aimed to investigate the connection between creative marketing and the financial performance of small and medium enterprises (SMEs) in Nyamata Town, Rwanda, as there is limited existing research on this topic. The research objectives included examining the factors influencing creative marketing and financial performance of SMEs, identifying the determinants of creative marketing and financial performance, and evaluating the relationship between creative marketing and financial performance in Nyamata Town. The study employed a mixed research approach, combining quantitative and qualitative methods. A sample of 69 respondents was selected using simple random and purposive sampling techniques, and data was collected through questionnaires and interviews. Primary data was analysed using SPSS version 26. On the determinants of creative marketing and financial performance of small medium enterprises, majority the participants 20 (30%) strongly agreed, 19 (28%) agreed, 4 (6%) that market selection was one of the determinants of creative marketing and financial performance of small medium enterprises. Majority the participants 13 (19%) agreed, and 14 (21%) that bureaucratic lending procedures affect creative marketing and financial performance of small medium enterprises in Nyamata Rwanda. There was a significant between creative marketing and financial performance since p (0.00) < 0.05. Thus, this concludes that creative marketing is a significant predictor of financial performance. The results revealed that timing and credit terms has a positive and statistically significant influence on financial literacy (β =.821: p = .003) which indicates that emphasizing financial literacy through setting aside funds and handling debt will increase one's capacity to start small businesses independently, increase the purchasing power of personal belongings, be able to manage debts, be free to make financial decisions, raise one's standard of living, be able to access health and other services, and be able to take on leadership roles. Basing on the findings and conclusion it is advised that social protection programs be implemented to teach individuals how to earn, spend, save, and invest their money as well as how to borrow money and protect it.